Infiltration of ozone guided with ultrasound in the brachial plexus for the treatment of the pain postamputación. Case Report (Ozone Therapy Global Journal, 2016)
Phantom pain referred to a lost limb and stump pain as a result of the amputation is considered as a form of chronic neuropathic pain that responds poorly to conventional therapeutic interventions, the physiological pain is derived from the neuroanatomical understanding of the nerve mechanism of pain and analgesia, It has been explained as neuronal plasticity invoking its action mechanism. The clinical case of a 58 year old man with partial removal of his left hand due to a traumatic etiology and a surgical stump.We describe a patient with phantom limb, painful phantom pain and stump, with poor response to physical and pharmacological therapy. The subject received infiltration of ultrasound-guided ozone in the brachial plexus supraclavicular route, as well as in the painful scar stump, with prior release of tissue using miniscalpel-needle, the patient evolved successfully and presented a best adjuvant analgesic response with the drugs.